Employee Advocacy in The Digital Era: The Roles of Employer Branding and EVP in Indonesia - Alice Leonardi Liong; Michael Christian (International Journal Labs, 2026)
This study examined whether employer branding (EB) and employee value proposition (EVP) increase employee advocacy (EA) among teaching and non-teaching staff in an Indonesian education network, and whether digital literacy (DL) strengthens these relationships in a work context where communication and advocacy are increasingly mediated by digital platforms. A cross-sectional survey was administered to 320 employees and analyzed using PLS-SEM with SmartPLS 4.1.1.6, including measurement model evaluation (reliability and validity) and structural model testing with interaction terms to assess moderation effects. EB and EVP showed positive and significant effects on EA, indicating that a compelling employer image and a strong employment value offering are associated with stronger employee willingness to advocate for the organization. In contrast, DL did not significantly moderate the EB–EA and EVP–EA relationships, suggesting that advocacy in this setting is shaped more by motivational and relational factors than by employees’ perceived digital capability. The study extends the employee advocacy literature by empirically positioning EA as an outward-facing behavioral outcome of EB and EVP in an emerging-economy education context, while also providing evidence that digital literacy despite high levels among respondents may not function as a meaningful boundary condition for these relationships.